Pengaruh Kualitas Layanan, Persepsi Kemudahan, Dan Pengetahuan Nasabah Terhadap Minat Penggunaan Aplikasi Brimo - Ruslan, Fitriyani; Madjodjo, Farid; Astria, Nikita (Universitas Gorontalo, 2023)
This study aims to determine the effect of service quality, perceived convenience, and customer knowledge on interest in using the BRImo application at PT Bank Rakyat Indonesia Soasio Branch Office. Methods of data analysis using multiple regression analysis, measuring scale using a Likert scale. The results showed that the service quality variable had a positive but not significant effect on interest in using the BRImo application. the perceived convenience variable has a significant positive effect on the intention to use the BRImo application and the customer knowledge variable has a significant positive effect on the intention to use the BRImo application. and variables namely service quality (X1), perceived ease of use (X2), and customer knowledge (X3) simultaneously have a significant effect on interest in using (Y) the BRImo application.